Non‐coding genetic variation in regulatory elements determines thrombosis and hemostasis phenotypes. (23rd May 2022) - Stefanucci, Luca; Frontini, Mattia
Abstract: Since the early inception of genome‐wide association studies (GWAS), it became clear that, in all diseases or traits studied, most genetic variants are likely to exert their effect on gene expression mainly by altering the function of regulatory elements. At the same time, the regulation of the gene expression field broadened its boundaries, from the univocal relationship between regulatory elements and genes to include genome organization, long‐range DNA interactions, and epigenetics. Next‐generation sequencing has introduced genome‐wide approaches that have greatly improved our understanding of the general principles of gene expression. However, elucidating how these apply in every single genomic locus still requires painstaking experimental work, in which several independent lines of evidence are required, and often this is helped by rare genetic variants in individuals with rare diseases. This review will focus on the non‐coding features of the genome involved in transcriptional regulation, that when altered, leads to known cases of inherited (familial) thrombotic and hemostatic phenotypes, emphasizing the role of enhancers and super‐enhancers.